2020
DOI: 10.3390/cancers12071765
|View full text |Cite
|
Sign up to set email alerts
|

The CCL5/CCR5 Axis in Cancer Progression

Abstract: Tumor cells can “hijack” chemokine networks to support tumor progression. In this context, the C-C chemokine ligand 5/C-C chemokine receptor type 5 (CCL5/CCR5) axis is gaining increasing attention, since abnormal expression and activity of CCL5 and its receptor CCR5 have been found in hematological malignancies and solid tumors. Numerous preclinical in vitro and in vivo studies have shown a key role of the CCL5/CCR5 axis in cancer, and thus provided the rationale for clinical trials using the repurpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(219 citation statements)
references
References 199 publications
(392 reference statements)
6
191
0
1
Order By: Relevance
“…Chemokine C-C motif ligand 5 (CCL5), also known as Regulated upon Activation, Normal T-cell Expressed and Secreted (RANTES), mediates migration and chemotaxis of cells and is expressed by several cell types such as fibroblasts, epithelial cells, tumour cells and immune cells. Although CCL5 is implicated in tumour progression and its elevated levels are detected in several cancers, it also promotes anti-tumour immunity via the recruitment of T cells and dendritic cells to the TME 40 . Research has uncovered a role for CCL5 in KRAS-induced lung cancer, where it is involved in a cytokine circuit along with IL-6 and STAT3 driving tumorigenesis 41 .…”
Section: Kras-induced Inflammationmentioning
confidence: 99%
“…Chemokine C-C motif ligand 5 (CCL5), also known as Regulated upon Activation, Normal T-cell Expressed and Secreted (RANTES), mediates migration and chemotaxis of cells and is expressed by several cell types such as fibroblasts, epithelial cells, tumour cells and immune cells. Although CCL5 is implicated in tumour progression and its elevated levels are detected in several cancers, it also promotes anti-tumour immunity via the recruitment of T cells and dendritic cells to the TME 40 . Research has uncovered a role for CCL5 in KRAS-induced lung cancer, where it is involved in a cytokine circuit along with IL-6 and STAT3 driving tumorigenesis 41 .…”
Section: Kras-induced Inflammationmentioning
confidence: 99%
“…Similarly, release of the inflammatory chemokine C-C motif chemokine 5 (CCL-5) from TAMs induced migration of glioma cells in a process dependent on increases in cytosolic [Ca 2+ ] and phosphorylation of CaMKII [ 263 ]. Indeed, CCL-5 has previously been implicated in invasive behaviour and metastasis in a range of tumours, including prostate, bone, and breast cancers [ 264 ].…”
Section: Calcium Signalling and The Tumour Immune Microenvironmentmentioning
confidence: 99%
“…We found that the yellow module had the strongest correlation with CD8 + T cells in the TCGA-SKCM cohort (Cor = 0.69; P = 1e- 26 ). Based on these ndings, we supplemented the heat map of the correlation between the factors in the yellow module and CD8 + T cells and the yellow module ( Fig.…”
Section: Identi Cation Of Cd8 + T Cell In Ltration Modules and Genesmentioning
confidence: 77%
“…CCL5 is a chemokine expressed by T lymphocytes, macrophages, platelets, synovium broblasts, renal tubular epithelial cells and tumor cells [26] . Harlin et al found that CCL5 produced by melanoma cells helped chemokine recruitment of CD8 + effector T cells, and lack of key chemokines may limit CD8 + T cell migration, thereby limiting the effectiveness of anti-tumor immunity [27] .…”
Section: Discussionmentioning
confidence: 99%